The Antisense Transcriptomes of Human Cells - He, Yiping (2008)
Transcription in mammalian cells can be assessed at a genome-wide level, but it has been difficult to reliably determine whether individual transcripts are derived from the Plus- or Minus-strands of chromosomes. This distinction can be critical for understanding the relationship between known transcripts (sense) and the complementary antisense transcripts that may regulate them. Here we describe a technique that can be used to (i) identify the DNA strand of origin for any particular RNA transcript and (ii) quantify the number of sense and antisense transcripts from expressed genes at a global level. We examined five different human cell types and in each case found evidence for antisense transcripts in 2900 to 6400 human genes. The distribution of antisense transcripts was distinct from that of sense transcripts, was non-random across the genome, and differed among cell types. Antisense transcripts thus appear to be a pervasive feature of human cells, suggesting that they are a fundamental component of gene regulation.